Empowerment of Cattle Breeder Groups in an Effort to Improve Welfare through Fermented Feed Processing - Salam, Abdul; Hartini; Husni (Universitas Putra Indonesia YPTK Padang, 2025)
Sumbawa cattle play an important role in meeting the needs of local, regional, and national markets. However, the increase in demand has not been balanced with the quality of livestock, management skills, distribution network, and the fulfillment of meat quality standards according to SNI 3932-2008. Farmers still depend on wild feed whose nutrients do not support productivity, thus having an impact on health, fattening, and economic stagnation of livestock groups. This activity aims to identify problems, empower farmers, and formulate training strategies to improve independence and welfare. The output produced is in the form of a manual for processing silage and ammonia feed, utilizing traditional feed ingredients that are abundant during the rainy season and can be stored for 6-12 months. Feed fermentation technology training is expected to be able to increase productivity up to 1.5–2 times compared to before. In addition, the formation of livestock business groups with a good management system is carried out through socialization and workshops related to business management, product packaging, and selling price determination. The program is carried out through three stages: (1) preparation in the form of problem identification, coordination, and socialization with partners of the Keban Jamu Hamlet Hamiri Breeder Group; (2) implementation in the form of socialization, planting grass feed banks, as well as fermented feed training and business management; (3) monitoring and evaluation to assess the improvement of knowledge, skills, and marketing capabilities oriented to long-term livestock growth.